(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Indian Gems & Jewellery sector plays a crucial role in the economy by providing significant employment and forex earnings. It benefits from the low-cost, skilled labor available in India, making it highly competitive globally. In 2020, India held a 20.6% share of the global diamond export market, contributing around 7.5% to the GDP and 14% to total merchandise exports. The sector's prominence is underscored by its position as a top global exporter of diamonds, with 95% of the world's diamonds being exported from India.